2021
DOI: 10.1002/jsfa.11648
|View full text |Cite
|
Sign up to set email alerts
|

Performance of conventional and enhanced‐efficiency nitrogen fertilizers on potato tuber mineral composition and marketability

Abstract: BACKGROUND Potato is an essential crop for global food security, and its cultivation requires a significant amount of readily available nitrogen (N) to ensure tuber quality. Therefore, managing N with enhanced‐efficiency fertilizers becomes a potential strategy to meet the seasonal potato N demand. A 3 site‐years (SYs) study was conducted to assess the marketable attributes and mineral composition of table‐stock potato in response to N rates and fertilizers urea, ammonium sulfate and ammonium sulfate nitrate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
3
4
1
Order By: Relevance
“…The significant differences in Fe content, as in other micronutrients, can be attributed to the differences in soil properties as well as micronutrient contents of the experimental sites. The findings of Souza et al (2022) on differences in Fe, Zn, Cu, and Mn contents of potato grown in three different locations are in agreement with the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The significant differences in Fe content, as in other micronutrients, can be attributed to the differences in soil properties as well as micronutrient contents of the experimental sites. The findings of Souza et al (2022) on differences in Fe, Zn, Cu, and Mn contents of potato grown in three different locations are in agreement with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The P content in different locations was significantly higher in Artova, where many other nutrients were at their highest levels. The P content of potatoes grown in three different locations of Sao Paola, Brazil (ranging between 0.55 and 1.05 g kg −1 ) was lower ( Souza et al, 2022 ) than the P contents recorded in this study. The researchers indicated that high nitrogen applications reduced the P content of tubers while increasing tuber size.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Consequently, the soluble solids content during the SCS and LCS was 4%−20% and 8%−50% higher, compared to El Beidha and Naima, respectively. These findings align with previous studies by Soares et al (2016) on the cultivar Ágata, which reported a content of 5.75% at full physiological maturity, as well as by Souza et al (2022) in a fall-winter growing seasons and three site-years field study in São Paulo State, Brazil. Similarly, Ilahy et al (2019) observed soluble solids values ranging from 4.1 to 5.2 ˚Brix and from 4.6 to 6.8 ˚Brix in selected potato clones grown under two different growing seasons.…”
Section: Crop Sciencesupporting
confidence: 92%
“…Hel-gerud et al (2015) reported average TDM values from 19.1% to 28.1% for 240 potatoes from seven different cultivars obtained from either commercial suppliers or local potato processing industry. Souza et al (2022) observed a similar average tuber dry weight of 18.5% under different fertilization regimes during the fall-winter growing season in Brazil. Haverkort and Verhagen (2008) reported that daily growth is reduced above day/night temperatures of 27/15˚C due to increased respiration, with dry matter distribution mainly favoring foliage, and tuber dry matter concentration unacceptably low, especially for processing purposes.…”
Section: Crop Sciencementioning
confidence: 55%